2020
DOI: 10.1002/cti2.1185
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of extracellular vesicles reveals an immunogenic cargo in rheumatoid arthritis synovial fluid

Abstract: Objectives. Extracellular vesicles (EVs) from rheumatoid arthritis (RA) synovial fluid (SF) have been reported to stimulate the release of pro-inflammatory mediators from recipient cells. We recently developed a size exclusion chromatography (SEC)-based method for EV isolation capable of high-quality enrichments from human SF. Here, we employed this method to accurately characterise the SF EV proteome and investigate potential contributions to inflammatory pathways in RA. Methods. Using our SEC-based approach,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…These observations are consistent with our previous report detailing SEC as a method for obtaining high-quality EV enrichments from SF [ 10 ]. Previously, we demonstrated that RA patients with high-grade synovial inflammation have increased concentrations of SF EVs [ 11 ]. Consistent with this, we detected a 3.5-fold increase in the EV miRNA concentration per mL of SF in joints with high-grade inflammation ( p -value = 0.0017; Figure 1 C), suggesting the potential involvement of SF EV miRNAs in inflammatory processes in RA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These observations are consistent with our previous report detailing SEC as a method for obtaining high-quality EV enrichments from SF [ 10 ]. Previously, we demonstrated that RA patients with high-grade synovial inflammation have increased concentrations of SF EVs [ 11 ]. Consistent with this, we detected a 3.5-fold increase in the EV miRNA concentration per mL of SF in joints with high-grade inflammation ( p -value = 0.0017; Figure 1 C), suggesting the potential involvement of SF EV miRNAs in inflammatory processes in RA.…”
Section: Resultsmentioning
confidence: 99%
“…For example, PTEN is targeted by multiple miRNAs enriched in high- and low-grade inflammation, as well as four of the 10 most prevalent miRNAs across all patients. Considering our previous observation of significant increases in total SF EV numbers within RA joints with high-grade inflammation when compared to those with low-grade inflammation [ 11 ]—combined with the significant enrichment in total EV miRNA concentration from joints with high-grade inflammation seen here (3.5-fold; p -value = 0.0017)—EV miRNA levels within RA joints could have a profound effect on inflammatory activity, whereas differences in EV miRNA profiles between joints with high- and low-grade inflammation might make more subtle contributions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…EDIL3, the DEL-1-encoding gene, is a susceptibility locus in ankylosing spondylitis, a type of inflammatory arthritis that affects the vertebrae (65). Moreover, the DEL-1 protein is enriched in the synovial fluid of RA patients with low-level inflammation as compared to RA patients with high-level inflammation (66), suggesting that DEL-1 might play a protective role in human RA. These reports and our findings from the present study, therefore, suggest that DEL-1 may be a promising novel therapeutic for the treatment of inflammatory arthritis.…”
Section: Discussionmentioning
confidence: 99%